2019
DOI: 10.1016/j.jcm.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complex Versus Contrast Training on Steroid Hormones and Sports Performance in Male Soccer Players

Abstract: Objective: The purpose of this study was to compare the effects of a complex versus a contrast training regimen with steroid hormones and the performance of soccer players. Methods: Thirty-six professional male soccer players were randomly divided into 3 equal groups: complex training (n = 12; body mass index [BMI], 22.95 ± 1.76 kg/m 2 ), contrast training (n = 12; BMI, 22.05 ± 2.03 kg/m 2 ), and control (n = 12; BMI, 22.27 ± 1.44 kg/m 2 ). Players from the complex and contrast groups were trained for 6 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…After screening titles and abstracts for relevance, 516 articles were excluded with 31 full texts being retained. Further screening of articles based on our inclusion and exclusion criteria resulted in the inclusion of 10 studies in the meta-analysis (Maio Alves et al, 2010;Faude et al, 2013;Brito et al, 2014;Cavaco et al, 2014;García-Pinillos et al, 2014;Hammami et al, 2017aHammami et al, ,b, 2019Chatzinikolaou et al, 2018;Ali et al, 2019) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening titles and abstracts for relevance, 516 articles were excluded with 31 full texts being retained. Further screening of articles based on our inclusion and exclusion criteria resulted in the inclusion of 10 studies in the meta-analysis (Maio Alves et al, 2010;Faude et al, 2013;Brito et al, 2014;Cavaco et al, 2014;García-Pinillos et al, 2014;Hammami et al, 2017aHammami et al, ,b, 2019Chatzinikolaou et al, 2018;Ali et al, 2019) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…As maximal strength is strongly related to sprint, jump, and COD in male soccer players (Wisløff et al, 2004), improvements in maximal strength may be an additional and relevant benefit derived from CT. In addition, improvements in sprint, jump, and COD performance after CT may be related to hormonal (Beaven et al, 2011;Ali et al, 2019) (e.g., testosterone increase) and cellular adaptations favorable to strength-power generation. For example, type IIx muscle fibers (i.e., those with greater contraction velocity, power, and rate of force development compared to type IIA and type I fibers) (Bottinelli et al, 1996;Harridge et al, 1996) may be favorably affected (i.e., greater preservation) by CT, even when compared to RT (Stasinaki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a need to aggregate data from the available literature to draw statistical inferences on the effects of plyometric jump training vs. traditional resistance training on skeletal muscle hypertrophy when there are a sufficient number of studies on the topic. Moreover, given that the combination between plyometric jump training and traditional resistance training favors an anabolic hormonal milieu ( Beaven et al, 2011 ; Ali et al, 2019 ), it would be relevant to determine optimal combination strategies between plyometric jump training and traditional resistance training to maximize skeletal muscle hypertrophy.…”
Section: Future Research Perspectivesmentioning
confidence: 99%
“…In football, contrast and complex training research found no negative results in terms of performance. These exercises are known to be based on the PAP effect (Ali et al, 2019). Considering the presence of many factors affecting the formation of the PAP effect, it may be a logical approach to evaluate physical parameters based on elements such as exercise intensity, repetition numbers, exercise choices, and age.…”
Section: The Effect Of Contrast and Complex Training On Sports Performancementioning
confidence: 99%
“…However, no significant difference in the longdistance sprint, repeat sprint, and agility parameters have been reached (Chatzinikolaou et al, 2018). In a study conducted by Ali et al, contrast and complex training were compared (Ali et al, 2019). For complex training, a 3-set plyometric exercise was performed following a 3-set high-intensity strength exercise.…”
Section: The Effect Of Contrast and Complex Training On Sports Performancementioning
confidence: 99%